Softening and hardening of yield stress by hydrogen–solute interactions. Issue 6 (21st February 2017) - Tehranchi, A.; Yin, B.; Curtin, W. A.
Abstract: Hydrogen atoms have a wide variety of effects on the mechanical performance of metals, and the underlying mechanisms associated with effects on plastic flow and embrittlement remain to be discovered or validated. Here, the reduction in the plastic flow stress (softening) due to hydrogen atoms in solute-strengthened metals, previously proposed by Sofronis et al. is demonstrated at the atomistic level. Glide of an edge dislocation through a field of solutes in a nickel matrix, both in the absence of hydrogen and in the presence of H bound to the solutes, is modelled. The 'solutes' here are represented by vacancies, enabling use of accurate binary Ni–H interatomic potentials. Since vacancies have a misfit strain tensor in the Ni matrix and also bind hydrogen atoms, they are excellent surrogates for study of the general phenomenon. The binding of H to the solute (vacancy) reduces the misfit volume to nearly zero but also creates a non-zero tetragonal distortion. Solute strengthening theory is used to establish the connection between strength and solute/hydrogen concentration and misfit strain tensor. Simulations show that when a dislocation moves through a field of random vacancy 'solutes', the glide stress is reduced (softening) when H is bound to the solutes. Trends in the simulations are consistent with theory predictions. Trends of softening or hardening by H in metal alloys can thus be made by computing the misfit strain tensor for a desired solute in the chosen matrix with and without bound hydrogen atoms. Pursuing this, density functional theory calculations of the interaction of H with carbon and sulphur solutes in a Ni matrix are presented. These solutes/impurities do not bind with H and the complexes have larger misfit strains, indicative of H-induced strengthening rather than softening for these cases. Nonetheless, H/solute interactions are the only mechanism, to date, that shows nanoscale evidence of plastic softening due to hydrogen associated with the hydrogen-enhanced localised plasticity concept in fcc metals.